Stem cell-dependent therapies : mesenchymal stem cells in chronic inflammatory disorders - Gross, Gerhard, 1949-; Häupl, Thomas (De Gruyter, 2013)
This book investigates the current state of the MSC-dependent therapy of chronic inflammatory disorders and autoimmune diseases. Among the covered topics are GvHD, chronic kidney, liver and lung disease, ischemic heart and inflammatory bowel disease, diabetes, osteoarthritis, various rheumatic and neurological disorders, tumors and solid organ transplantations.